Evaluation of the Pre-Startup Safety Review Effectiveness (PSSR) in Process Industries: a Gas Refinery Case Study - Ahmad Soltanzadeh (International Journal of Occupational Hygiene, 2019)
Industrial accidents that have occurred in oil and gas industries have always created trouble for these industries’ workers. The pre-startup and start-up of refineries accidents are one of the most critical challenges in this area. Therefore, this study was conducted to evaluate the effectiveness of the Pre-Startup Safety Review (PSSR) process and its compliance assessment. This descriptive-analytical study was carried out in a gas refinery in 2018. The study tools included the National Iranian Oil Company (NIOC) Guideline and the PSSR executive method in a gas refinery. Data analysis was performed via SPSS software version 22.0. The significance level in this study was considered 0.05. The results showed that the highest and lowest compliances were related to the accident management and emergency response (65%), readiness for assignment (12%). Also, the frequency rate of accidents showed a significant difference (p<0.001) between refineries which was performing PSSR and did not do this process. The findings indicated that PSSR implementation can play a significant role in controlling and reducing accidents, as well as stopping and interrupting process operations. Besides, PSSR checklist details more accurately implementation, helps the process of pre-startup safety review to be controlled better and be more productive.